2015
DOI: 10.1371/journal.pone.0143823
|View full text |Cite
|
Sign up to set email alerts
|

Rationale, Design and Methods of the Ecological Study of Sexual Behaviors and HIV/STI among African American Men Who Have Sex with Men in the Southeastern United States (The MARI Study)

Abstract: BackgroundThis paper describes the rationale, design, and methodology of the Ecological Study of Sexual Behaviors and HIV/STI among African American Men Who Have Sex with Men (MSM) in the Southeastern United States (U.S.; known locally simply as the MARI Study).MethodsParticipants are African American MSM aged 18 years and older residing in the deep South.ResultsBetween 2013 and 2015, 800 African American MSM recruited from two study sites (Jackson, MS and Atlanta, GA) will undergo a 1.5-hour examination to ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…While multi-city survey studies have been conducted among Black MSM in the Deep South [43], this is the first study utilizing GPS methods to be conducted among any sample of Black MSM in the Deep South and one of few studies in the literature to implement a two-week GPS protocol [15]. To our knowledge, this is the first study to complete a two-week GPS protocol among any sample of MSM.…”
Section: Discussionmentioning
confidence: 99%
“…While multi-city survey studies have been conducted among Black MSM in the Deep South [43], this is the first study utilizing GPS methods to be conducted among any sample of Black MSM in the Deep South and one of few studies in the literature to implement a two-week GPS protocol [15]. To our knowledge, this is the first study to complete a two-week GPS protocol among any sample of MSM.…”
Section: Discussionmentioning
confidence: 99%
“…All participants were part of a larger multisite study, the CDC-funded Minority HIV/AIDS Research Initiative (MARI) that examined interpersonal, intrapersonal, and environmental factors associated with HIV/STI infection among same-gender-loving Black men in the Southeastern United States. Full study details are reported elsewhere (Hickson et al, 2015). In brief, eligibility was restricted to participants who self-identified as African American, assigned male sex at birth, identified as a cisgender man, 18 years old or older, reported having had sex with a man in the past six months, and lived in Jackson.…”
Section: Methodsmentioning
confidence: 99%
“…(Kasperson et al, 1988: p. 141) The term 'riskscape' is commonly used to refer to places, or environments, associated with significant risk (Mair et al, 2011). Much of the riskscape literature takes a socioecological, and macro-level perspective to identify the set of individual, interpersonal, environmental and political factors that increase vulnerability to hazards (Cutter, 1996) or poor health (Morello-Frosch et al, 2001;Morello-Frosch and Shenassa, 2006;Hickson et al, 2015;Mair et al, 2011). What the riskscape literature lacks, however, are studies that explore how perception of risk contributes to the construction of the riskscape, as well as influences how it is navigated at a microlevel.…”
Section: Analytical Focus: Navigating 'Riskscapes'mentioning
confidence: 99%